Keberhasilan Mediator dalam Mendamaikan Sengketa Perkara Cerai Gugat di Pengadilan Agama Bogor - Fitri, Azkia Rahmania; Nawawi, M. Kholil; Hamdani, Ikhwan (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstracts: Mediation is a peaceful dispute resolution effort aimed at preventing divorce, particularly in divorce lawsuit cases at the Bogor Religious Court. The increasing number of divorces each year reflects that many husband and wife couples fail to resolve conflicts independently, thus requiring assistance from mediators to achieve more solution-oriented settlements. This condition makes mediation an important alternative in resolving family conflicts before proceeding to legal rulings. From the perspective of Islamic law and legislation, mediation is viewed as an appropriate step in maintaining family integrity. This research aims to identify the strategies employed by mediators and the success rate of mediation in handling divorce lawsuits. The study uses a qualitative approach with a descriptive-analytical method and field research type. The results show that mediators implement various strategies, such as initial approaches (rapport building), caucus techniques, flexible time management, strategy adjustments based on the plaintiff, and providing advice through religious, cultural, and psychological approaches. However, the success rate of divorce lawsuit mediation remains relatively low, with only 43 out of 125 cases successfully resolved, corresponding to a success percentage of 34.4%. Factors contributing to failure include the absence of one party and high levels of emotion and ego. Supporting factors include the patience and perseverance of mediators, the length of the marriage, the presence of children, mediator competence, and good faith from the parties involvedKeywords: Mediation, Divorce Lawsuit, Religious Court, Mediator Strategies, Mediation Success, Dispute Resolution. Abstrak : Mediasi merupakan upaya penyelesaian sengketa secara damai yang bertujuan untuk mencegah terjadinya perceraian, khususnya dalam perkara cerai gugat di Pengadilan Agama Bogor. Meningkatnya angka perceraian setiap tahun mencerminkan bahwa banyak pasangan suami istri yang gagal menyelesaikan konflik secara mandiri, sehingga memerlukan bantuan dari mediator untuk mencapai penyelesaian yang lebih solutif. Kondisi ini menjadikan mediasi sebagai alternatif penting dalam menyelesaikan konflik rumah tangga sebelum berlanjut ke putusan hukum. Dalam perspektif hukum Islam dan peraturan perundang-undangan, mediasi dipandang sebagai langkah yang tepat dalam menjaga keutuhan keluarga. Penelitian ini bertujuan untuk mengetahui strategi yang digunakan oleh mediator serta tingkat keberhasilan mediasi dalam menangani perkara cerai gugat. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analisis dan jenis penelitian lapangan (field research). Hasil penelitian ini adalah bahwa mediator menerapkan berbagai strategi, seperti pendekatan awal (rapport building), teknik kaukus, pengelolaan waktu yang fleksibel, penyesuaian strategi berdasarkan pihak penggugat, serta pemberian nasihat melalui pendekatan keagamaan, budaya, dan psikologis. Meskipun demikian, tingkat keberhasilan mediasi cerai gugat masih tergolong rendah, yakni hanya 43 dari 125 perkara yang berhasil diselesaikan, dengan persentase keberhasilan sebesar 34,4%. Faktor penyebab kegagalan antara lain ketidakhadiran salah satu pihak serta tingginya emosi dan ego. Adapun faktor pendukung meliputi kesabaran dan ketekunan mediator, lamanya usia pernikahan, kehadiran anak, kompetensi mediator, serta itikad baik dari para pihak.Kata kunci: Mediasi, Cerai Gugat, Pengadilan Agama, Strategi Mediator, Keberhasilan Mediasi, Penyelesaian Sengketa.